Evaluation of antibiotic and cell-based therapy in preventing S. epidermidis-induced nonunion in rats. (International Journal of Health, Animal Science and Food Safety, 2016)
Methicillin-resistant S. epidermidis (MRSE) is responsible for biofilm-related infections (Montanaro,2011; Romanò, 2013) and fracture nonunion, as recently demonstrated by our group (Lovati, 2016).The present study aims to investigate the efficacy of antibiotic or cell-based therapies in preventingbacterial infections and nonunion establishment.Under anesthesia, femoral fractures were performed in 30 rats, then the site of injury was injectedwith a clinical-derived MRSE strain and, finally, synthesized with stainless steel plates. Rats weredifferently treated as follows: MRSE-infected controls (IC); systemically-injected vancomycin (s-VANC);local vancomycin-enriched hydrogel (l-HYD); systemically-injected BMSCs (s-BMSCs); and locallyinjectedBMSCs (l-BMSCs).After 6 weeks, pro-inflammatory cytokines, quantitative micro-CT, histological and microbiologicalanalyses were carried out to investigate the host response to the different treatments.Half of the s-BMSCs rats died closely to the systemic cell injection, thus excluded for further analyses.Our results for the IC group were consistent with previously published data (Lovati, 2016), showingsigns of osteomyelitis and nonunion development. In s-VANC and l-HYD groups, micro-CT detected agood bony bridging and the microbiological counts were significantly lower with respect to the othergroups. Our study suggests that the association of s-VANC and l-HYD is an effective treatment toprevent biofilm-induced nonunions. Differently, we cannot positively support cell therapies for thispurpose due to the high risk related to the systemic cell injection, thus requiring further studies to beeventually proposed in clinics.
Keywords: Methicillin-resistant S. epidermidis; nonunion; mesenchymal stem cells; rat model; osteomyelitis